New Progress in the Molecular Regulations and Therapeutic Applications in Cardiac Oxidative Damage Caused by Pressure Overload - Xiaomeng Shi; Arin Dorsey; Hongyu Qiu (MDPI AG, 2022)
Chronic pressure overload is a key risk factor for mortality due to its subsequent development of heart failure, in which the underlying molecular mechanisms remain vastly undetermined. In this review, we updated the latest advancements for investigating the role and relevant mechanisms of oxidative stress involved in the pathogenesis of pressure-overload-induced cardiomyopathy and cardiac dysfunction, focusing on significant biological sources of reactive oxygen species (free radical) production, antioxidant defenses, and their association with the cardiac metabolic remodeling in the stressed heart. We also summarize the newly developed preclinical therapeutic approaches in animal models for pressure-overload-induced myocardial damage. This review aims to enhance the current understanding of the mechanisms of chronic hypertensive heart failure and potentially improve the development of better therapeutic strategies for the associated diseases.